Comparative Evaluation of Hospital Environmental Performance based on ISO 14031 Evaluation Model - maryam mazaheri; yousef babayi mesdaraghi; arezoo alizadeh (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Hospitals are working to create innovation in patient care throughout the world while maintaining high quality standards. Since in implementing this innovation, hospitals have an impact on the natural environment, hospital managers are constantly developing management plans to conserve energy and dispose medical waste properly to reduce the damage to patients, surrounding communities, and the natural environment. Therefore, this study evaluated the important and effective indicators in order to target the measures in the field of hospital environmental management. Methods: This cross-sectional analysis was designed and implemented in 2018 and 2019 in Trita subspecialty hospital in the west of Tehran. To implement this study, ISO 14001 standard was used and ISO 14031 standard was applied to monitor it. Results: According to the findings, 18 important and basic indicators were defined in the field of environmental performance for the hospital and the relevant indicators were measured. Correction and improvement of indicators was clearly observed in 2018 and 2019. Most of the corrective actions and the most noticeable changes were related to waste. Conclusion: The use of environmental assessment models along with managerial support for corrective action can protect the environment in the long run and improve public health. Moreover, proper management of the hospital waste can reduce the costs.